Meningkatkan Motivasi Belajar Al-Qur’an Surat At-Tin Siswa Kelas IV SD Negeri 14 Tonang Raya Kecamatan Dua Koto Melalui Model Cooperatif Learning - Nurasmi, Nurasmi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to determine the effect of applying the Cooperative Learning model in enhancing students’ motivation to learn the Qur’an, specifically on the topic of Q.S At-Tin, among fourth-grade students at SD Negeri 14 Tonang Raya, Nagari Simpang Tonang, Dua Koto District. The identified problem was the low learning enthusiasm of students in the Islamic Education and Character Education subject due to the monotonous lecture-based teaching method. In this study, the Cooperative Learning model was implemented to create a more engaging, active, and collaborative learning environment. The results of the study are expected to contribute to improving students’ learning motivation and outcomes, particularly in reading Q.S At-Tin. This research concludes that the Cooperative Learning approach has the potential to significantly enhance students’ motivation and learning achievements.